United Artists : the company built by the stars. Volume 1. 1919-1950 - Balio, Tino. (Madison, Wis. : University of Wisconsin Press, 2009)
Annotation United Artists was a unique motion picture company in the history of Hollywood. Founded by Charlie Chaplin, Mary Pickford, Douglas Fairbanks, and director D.W. Griffithfour of the greatest names of the silent eraUnited Artists functioned as a distribution company for independent producers. In this lively and detailed history of United Artists from 1919 through 1951, film scholar Tino Balio chronicles the companys struggle for survival, its rise to prominence as the Tiffany of the industry, and its near extinction in the 1940s. This edition is updated with a new introduction by Balio that places in relief UAs operations for those readers who may be unfamiliar with film industry practices and adds new perspective to the companys place within Hollywood.
Appendix 4 Income HistoryAppendix 5 Record of Dividend Payments; Appendix 6 Capital Stock Purchased by the Company; The UA Collection: A Descriptive Inventory; Notes; Index.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: United Artists Corporation -- History; United Artists Corporation; Motion picture industry -- History; Cinéma -- Industrie -- Histoire; BUSINESS & ECONOMICS -- Industries -- Media & Communications; TECHNOLOGY & ENGINEERING -- Telecommunications; Motion picture industry; History